In-depth investigation on the photostability and charge separation mechanism of Ag3PO4/g-C3N4 photocatalyst towards very low visible light intensity - Mukhair, Hayati; Halim Abdullah, Abdul; Adlan Mohd Hir, Zul; Syazwani Osman, Nur; Zainal, Zulkarnain; Hong Ngee, Lim (Elsevier, 2023)
A facile chemical precipitation approach was used to synthesis visible light-driven Ag3PO4/g-C3N4 photocatalysts, with varying g-C3N4 content. The photostability performances were tested against methylorange (MO) dye removal using very low light intensity (23 W). The fabrication of g-C3N4 onto Ag3PO4 surface has resulted in a substantial enhancement in the photostability and performance of pristine Ag3PO4. The Ag3PO4/g-C3N4, with a ratio of 1:0.03, displayed a rapid and almost a complete photoremoval efficiency within 10 min under normal conditions. The improved activities under visible irradiation were attributed to the photoexcited carrier’s outstanding separation efficiency as demonstrated by the band gap, photoluminescence spectra, and cyclic voltametric studies. Positive holes (h+) and superoxide radicals’ anions (O2) were found to be the dominant species responsible for the degradation via the Z-scheme mechanism.